2011
DOI: 10.1111/j.1540-8167.2011.02141.x
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant Therapy and Risk of Cerebrovascular Events After Catheter Ablation of Atrial Fibrillation in the Elderly

Abstract: The risk of a periprocedural CVE after RFA of AF is similar among patients ≥65 and <65 years old. Late CVEs after RFA are more prevalent in older than younger patients with AF, and age >75 years old is the only independent predictor of late CVEs regardless of the rhythm, anticoagulation status, or the CHADS(2) score (Congestive heart failure, Hypertension, Age ≥ 75 years, Diabetes mellitus and prior Stroke or transient ischemic attack).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 19 publications
2
65
2
1
Order By: Relevance
“…A current survey in Canada also found that physicians are likely to discontinue OAC when there is no evidence for arrhythmia recurrence [12]. As to be expected and in line with previous studies [8], withdrawal of OAC occurred more often in low-risk patients. Still, these patients had a mean CHADS 2 -Score of 0.7 ± 0.7 and were thus predominantly recommended to receive ongoing OAC after AF-ablation regardless of the procedural outcome.…”
Section: Main Findingssupporting
confidence: 52%
See 1 more Smart Citation
“…A current survey in Canada also found that physicians are likely to discontinue OAC when there is no evidence for arrhythmia recurrence [12]. As to be expected and in line with previous studies [8], withdrawal of OAC occurred more often in low-risk patients. Still, these patients had a mean CHADS 2 -Score of 0.7 ± 0.7 and were thus predominantly recommended to receive ongoing OAC after AF-ablation regardless of the procedural outcome.…”
Section: Main Findingssupporting
confidence: 52%
“…Still, most of these studies only included patients with a low CHADS 2 -Score and therefore a low risk for TE. Only Guiot et al [8] included patients aged C65 years, thus having an increased risk for TE. The annual stroke rate after AF-ablation in this cohort was 1.1 %.…”
Section: Introductionmentioning
confidence: 98%
“…A limitation of these studies is that most patients had previously failed treatment with at least one antiarrhythmic medication. There are several published studies that have reported a low risk of stroke in patients who discontinue systemic anticoagulation several months or more following AF ablation [114][115][116][117]. These findings need to be interpreted with caution, however, because AF can recur early or late after AF ablation and recurrences are more likely to be asymptomatic following, compared with prior to, AF ablation.…”
Section: Rationale For Eliminating Atrial Fibrillation With Ablationmentioning
confidence: 81%
“…26 Although that study did confirm a higher stroke risk for older patients (age >75 years had odds ratio (OR) 4.9, highest during the first year after ablation, but remained steady in subsequent years (Figure 2).…”
Section: Longer-term Outcomesmentioning
confidence: 94%